2014
DOI: 10.1371/journal.pone.0112257
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between Patient Self-Reports and Claims Data on Clinical Diagnoses, Medication Use, and Health System Utilization in Taiwan

Abstract: PurposeThe aim of this study was to evaluate the concordance between claims records in the National Health Insurance Research Database and patient self-reports on clinical diagnoses, medication use, and health system utilization.MethodsIn this study, we used the data of 15,574 participants collected from the 2005 Taiwan National Health Interview Survey. We assessed positive agreement, negative agreement, and Cohen's kappa statistics to examine the concordance between claims records and patient self-reports.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
208
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(218 citation statements)
references
References 25 publications
9
208
1
Order By: Relevance
“…To our knowledge, this is the first study to compare DMT use, product, and adherence between self-report and pharmacy records in MS.Previous research on antidepressant [27] and general medication use [28] found substantial agreement (kappa of 0.69 and 0.64, respectively) between self-report and claims records in terms of drug use. We found near-perfect agreement between sources, suggesting that self-report truly reflects the actual DMT received.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, this is the first study to compare DMT use, product, and adherence between self-report and pharmacy records in MS.Previous research on antidepressant [27] and general medication use [28] found substantial agreement (kappa of 0.69 and 0.64, respectively) between self-report and claims records in terms of drug use. We found near-perfect agreement between sources, suggesting that self-report truly reflects the actual DMT received.…”
Section: Discussionmentioning
confidence: 85%
“…As was the case in this study, multivariate analysis of the data from this probability survey estimated that hypertension and diabetes were significant risk factors for ED after controlling for age and other characteristics . Concordance between real‐world observational data and population survey epidemiological data has been variable in recent studies of other healthcare topics, including diabetes prevalence, myocardial infarction prevalence, in vitro fertilisation usage rates, mental health visit frequency, asthma medication possession, and clinical diagnosis, medication use and healthcare utilisation . Several factors may account for the differences in outcomes, including recall and non‐response bias, coding errors and self‐reported symptoms vs EHR or claims‐based diagnosis or treatment.…”
Section: Discussionmentioning
confidence: 99%
“…All T2DM patients met the following criteria: (1) minimal four outpatient visits for T2DM, and (2) prescription of glycemic‐lowering drugs. The accuracy of T2DM diagnosis in this dataset has been validated . The index hospitalization was defined as that during which the patient was admitted for hip fracture surgery.…”
Section: Methodsmentioning
confidence: 99%